ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI INTENSITAS PILIHAN TINGGAL (Kasus di Perumahan Kelurahan Beringin Semarang) - Galifta Twin Anjani; Bagio Mudakir (Universitas Diponegoro, 2012)
Intensity of Choice Living is activities conducted by individuals as the final consumer and business customers that result in a decision to make the choice and use of products or services. This study aims to determine the effect of land and building taxes, location, facilities, environment and purchase price of the intensity of choice living to stay at Beringin sub-district Semarang. The population in this study are 5 houses in Beringin sub-district Semarang by the number of data transactions in the year 2011 as many as 277 transactions, with the number of samples by 73 respondents. Sampling technique in this study is stratified random sampling. Data collection methods used were a questionnaire, while to process the data used Tobit analysis techniques with the Shazam software for windows. The results showed that the Land and building tax has no effect on the intensity of choice living, meaning that the low property tax that is applied does not affect the intensity of choice to live, with a value is -0.98249 t-ratio> -1.294. Location of the intensity of choice living is significantly positive, meaning that the strategic location of housing offered, the more it will increase the intensity of choice to live, with a value is 2.0517 t-ratio> 1.294. Facilities influence for intensity of choice living is significantly positive, meaning that the more adequate housing facilities provided by the more it will increase the intensity of choice living, with a value is 1.8918 t-ratio> 1.294. Environmental influences for intensity of choice living is significantly positive, meaning that if the environment is conducive to housing, then it will increase the intensity of the residents living options, with a value is 2.3092 t-ratio> 1.294. Influence from the intensity of choice living for purchase price is significantly negative, meaning the lower the purchase price of the house, it affects the intensity of choice living, with a t-ratio value is -3.4125 <-1.294. These findings indicate that policies can be done by the developers and the government is focusing on four factors.